THE INFLUENCE OF LEADERSHIP STYLE, MOTIVATION, WORK DISCIPLINE AND USE OF TECHNOLOGY ON TEACHER PERFORMANCE DURING THE COVID-19 PERIOD IN TENJOLAYA DISTRICT - Puji Astuti; Amir Tengku Ramly; Immas Nurhayati (ITB AAS Indonesia Surakarta, 2023)
Abstract Performance is one important element in the organization.The purpose of this study is to create a regression model between leadership style, motivation, and work discipline together on the performance of private vocational school teachers in Tenjolaya sub-district during the Covid-19 period. This research is classified as qualitative research. The data collection tool in this study was a questionnaire. While the data analysis techniques used descriptive analysis techniques, inferential statistical data analysis, and multiple linear regression analysis techniques. The results of this study conclude that there is a positive and significant influence between Leadership Style, Motivation, Work Discipline, and Information Technology on Performance. The results of the multiple linear regression equation regarding the influence of social media and socialization on public health behavior are Y: 2,784 – 0.508 X1 – 0, 490 X2 – -005 X3 – 0.771 X4. Meanwhile, the R Square value obtained is only 0.681 or 68.8%, and 33.4% is explained by other variables that are not included in the regression model. further research on leadership style, work discipline, and motivation because information technology and motivation are good enough to improve teacher performance during the covid-19 period Keywords: Leadership Style, Motivation, Work Discipline, Use Technology, Performance